TARI PIWURUK DALAM PENCIPTAAN FOTOGRAFI ESAI - Nur Shintya, Anugrah; Akbar Pahala, Agam (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2024)
This study aims to revive public enthusiasm for dance art in the post-pandemic era through a photographic essay of Tari Piwuruk, using a practice-led research approach. The creative concept combines: (1) pragmatic art, (2) figurative forms, and (3) contemporary aesthetics. The process includes movement exploration, motion blur photography, and the construction of a visual narrative. The result is a photographic work that presents the dynamics of dance in an innovative way while conveying a message of resilience.